PELESTARIAN BAHASA BALI DALAM MEDIA CETAK BERBAHASA BALI: KAJIAN SOSIOLINGUISTIK - Ita Ryandewi, Anak Agung Istri (Humanis; Volume 15. No.2. Mei 2016)
Research of "Pelestarian Bahasa Bali dalam Media Cetak Berbahasa Bali: Kajian Sosiolinguistik" is a study about preservation of the language through printed media. The purpose of this study is to examines the diversity of languages, the factors that influence the writing of different languages, the factors supporting and inhibiting efforts to preserve the Balinese. The theory used in this research is the theory of sociolinguistics with sub theory of preservation. Methods and techniques used in data collection is reference method aligned with the observation method with advanced technique. Furthermore, in presenting the data is done by informal methods. The technique used is the technique of inductive and deductive thinking. The usage of the Balinese languages diversity in the printed media such as at BU and short stories have differences in usage manifold. In BU tends to use BBA because BBA is Balinese that is more appropriate language to use in front of the audiences. While in the short story the usage of variation language more varied. Factors that affect the diversity writing is the accuracy of spelling or diction, writing letters, accuracy of spelling and usage of uptake word. The Factors that supporting the preservation of Balinese in Printed media enthusiastic of community to involve in column that is published in the media BO and MS. Inhibiting factors of Balinese in Balinese-printed media consisted of limited portions of the page, loading the frequency of news, and the human resourcesfactor
Keywords: language preservation, mass media, Balinese-printed media